(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to select the best tillage andsowing methods for large scale production of wheat in the Northern Stateof Sudan. Eight treatments comprising five tillage methods (Discploughing + disc harrowing + leveling; moldboard ploughing + discharrowing + leveling; chisel ploughing + disc harrowing + leveling; lightoffset disc harrowing + leveling; zero tillage as control) and three sowingmethods (manual broadcasting + cultivation; manual broadcasting + lightdisc harrowing; seed drilling on flat land) were compared in a split-plotdesign arrangement for two seasons (2000/ 01 and 2001/ 02). The greatestaverage yields were obtained by using disc plough + disc harrow +leveling (4.0 ton/ha) and chisel plough + disc harrowing + leveling (3.9ton/ha) compared with other tillage methods. Seed drilling as well ascultivation after broadcasting resulted in significantly (P<0.01) higheraverage yields (3.9 ton/ha) than harrowing after broadcasting for the twoseasons